Money Politics In Madiun City During Local Elections Poses A Threat to Local Democracy - Caroline Magdalena; Muhammad Hardi Ares bin Saufi; Lintang Mutiara Dewi (PT Pro Panoramic Solution, 2025)
The phenomenon of money politics often occurs in local elections in any city, including in Madiun City, posing a serious threat to local democracy. Through local elections, the community hopes to elect leaders who are qualified and in line with the will the people. However, in practice, various forms of fraud, dishonesty, and deception are often encountered during a campaign, including the practice of bribing the public with money or goods to vote for a particular candidate, a practice known as political corruption. This study focuses on the city of Madiun, serving as the primary subject and object of analysis to examine and analyze the occurrence of political corruption in local elections. The objective of this study is to analyze the occurrence of money politics in the local election of Madiun City and to examine the factors that drive this phenomenon in Madiun City. The method used in this study is a quantitative approach focused on data collection and analysis. This approach is also used to understand the extent of the influence of money politics on society and its impact on local democracy. The method involved conducting a survey using a questionnaire designed to collect data from a large number of respondents using sampling techniques from the voter population in Madiun City, and analyzing the collected data. The results of this study indicate that money politics practices pose a serious threat to local democracy in Madiun City